2021
DOI: 10.1021/acs.orglett.1c04139
|View full text |Cite
|
Sign up to set email alerts
|

Radical Perfluoroalkylation Enabled by a Catalytically Generated Halogen Bonding Complex and Visible Light Irradiation

Abstract: Exploiting charge-transfer complexes in visible light-promoted single-electron redox reactions is a promising route for opening novel synthetic pathways, and catalytic approaches to complex formation are critical for facilitating this chemistry. This report describes the use of a substituted hydroquinone catalyst to promote radical perfluoroalkylation reactions. Mechanistic studies indicate that the reaction is initiated through formation of a visible light-absorbing halogen bonding complex between the hydroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Very recently, the Pitre group reported a general method for the perfluoroalkylation of (hetero)arenes catalyzed by hydroquinone through the formation of an EDA complex with perfluoroalkyl iodides. [68] Using a catalytic amount of a specific di-tert-butylated hydroquinone under basic conditions, they were able to functionalize a series of (hetero)arenes with fair to good yields (Scheme 26, Equation (1)). The proposed mechanism would involve the formation of an EDA complex between the catalyst and the perfluoroalkyl iodide, irradiation of which would generate a perfluoroalkyl radical species that can then add to the electron rich (hetero)arene to give an intermediate that would undergo a hydrogen atom transfer reaction with the hydroquinone radical intermediate formed after irradiation to give the perfluoroalkylated (hetero)arene and regenerate the catalyst (Scheme 26, Equation (2)).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the Pitre group reported a general method for the perfluoroalkylation of (hetero)arenes catalyzed by hydroquinone through the formation of an EDA complex with perfluoroalkyl iodides. [68] Using a catalytic amount of a specific di-tert-butylated hydroquinone under basic conditions, they were able to functionalize a series of (hetero)arenes with fair to good yields (Scheme 26, Equation (1)). The proposed mechanism would involve the formation of an EDA complex between the catalyst and the perfluoroalkyl iodide, irradiation of which would generate a perfluoroalkyl radical species that can then add to the electron rich (hetero)arene to give an intermediate that would undergo a hydrogen atom transfer reaction with the hydroquinone radical intermediate formed after irradiation to give the perfluoroalkylated (hetero)arene and regenerate the catalyst (Scheme 26, Equation (2)).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Very recently, the Pitre group reported a general method for the perfluoroalkylation of (hetero)arenes catalyzed by hydroquinone through the formation of an EDA complex with perfluoroalkyl iodides [68] . Using a catalytic amount of a specific di‐ tert ‐butylated hydroquinone under basic conditions, they were able to functionalize a series of (hetero)arenes with fair to good yields (Scheme 26, Equation (1)).…”
Section: Perfluoroalkylation Of (Hetero)arenesmentioning
confidence: 99%
“…3 a ,5 Since 2019, the EDA catalysis strategy, i.e. EDA complex-mediated radical generation with catalytic amounts of electron donors 6–9 or acceptors, 10 has emerged as a rapidly growing subfield. Since the donor or acceptor catalyst functions through the association with leaving group-bearing moieties, the EDA catalysis approach is selective and efficient as was demonstrated in the pioneering studies.…”
Section: Introductionmentioning
confidence: 99%
“…Currently known donor catalysts include anion donors, 6,7 neutral lone pair donors 8 and π donors 9 (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…12 During the preparation of our manuscript, Pitre and co-workers found that hydroquinones were suitable XB catalysts for radical perfluoroalkylation under visible light irradiation. 13 On the other hand, Walker, Legon and co-workers established the XB of water and CF 3 I (Scheme 1C). 14 In this study, we drew inspiration from these elegant studies and our previous development of σ-hole effect directed photolysis.…”
Section: Introductionmentioning
confidence: 99%